Characteristics of Asbuton Mix Using Geopolymer Fly Ash Coarse Aggregate as a Substitute for Natural Aggregates - I Dewa Made Alit Karyawan; Hasyim Hasyim; Desi Widianty; Ratna Yuniarti (Jurnal Penelitian Pendidikan IPA, 2023)
The increase in the number of road construction projects has led to an increase in the need for road pavement materials (aggregate and asphalt). Currently it takes about 1.6 million tonnes/year of asphalt, as well as aggregate. Seeing these conditions, it is necessary to anticipate the use of waste or natural resources that have not been utilized optimally. In this study, fly ash (PLTU waste) was used as aggregate and Asbuton (Buton Island rock asphalt) was used as a binder for the asphalt mixture. As an effort to save energy, the stirring system is cold. Based on the volumetric characteristics of the artificial coarse aggregate, it only meets the specifications for the VMA value, while the VIM and VFB values have not been met. The mechanical properties (stability and flow values) of the cold asphalt mixture on the replacement of natural aggregate with 25% artificial aggregate met the requirements, but did not meet the Marshall Quotien requirements